An Evaluation of the Measures to Reduce the Impact of Human Immunodeficiency Virus Infection and Acquired Immune Deficiency Syndrome in Zimbabwe and Report on the Achievements Made to Date - Tatenda T. Ngara (HIV/AIDS Research and Treatment-Open Journal, 2022)
The impact of human immunodeficiency virus infection and acquired immune deficiency syndrome (HIV/AIDS) on individuals, communities and organisations is a major bone of resentment the world over. Human capital planning (HCP) focuses on helping managers set the direction for an organisation in regard to its future. Human Resources needs but lamentably this is made difficult because of the HIV/AIDS pandemic which among other devastating effects is short life expectancy which leads to high turnover within organisations. To reduce this catastrophe, a collaborative effort has been made by International organisations, the government and the private sector to provide measures to fight the impact of HIV/AIDS. These measures have been largely effective and include initiatives such as obtaining. Political support by leaders, engaging multiple economic sectors, educating the youth on HIV/AIDS, fighting stigmatization, enhancing poverty and improving free counselling interventions just but to mention a few. The achievements brought by these measures to date in Zimbabwe include reduction of workplace discrimination against HIV/AIDS infected people, formation of the National AIDS Control Programme by the Ministry of Health in 1987 and implementation of a mandatory 3% AIDS levy to support HIV prevention.